Ownership concentration and financial policy of China's listed firms - Choi, Heejung; Kim, Ju Hyun; Suh, Jungwon; Yu, Shuilian (China Economic Review, 2023)
This study examines the role of ownership concentration, measured by the top-five shareholders' equity ownership, in shaping corporate finance policies in China. Among privately-owned enterprises (POEs), ownership concentration has negative and positive effects on their debt and cash reserves, respectively, consistent with controlling shareholders' incentives to stave off business failures and ride out adverse future circumstances. These effects are more pronounced if POEs have high market-to-book, suggesting that growth opportunities heighten their controlling shareholders' desire to avoid debt and hoard cash. Although ownership concentration has similar effects on debt and cash in state-owned enterprises (SOEs), these effects in SOEs appear to reflect management discretion or conservatism. Our evidence suggests that ownership concentration is a key driver of corporate finance in an emerging market, but private and state ownership concentrations have seemingly similar but qualitatively different consequences.
Keywords: Capital structure; Cash reserves; China; Management discretion; Ownership concentration; POEs; SOEs